Islam Barat dan Islam Timur dalam Peradaban Universal dan Lokal - Imam Mustakim (Journal on Education, 2024)
This study compares Western Islam and Eastern Islam within the context of universal and local civilizations. Western Islam, which developed in Europe and America, tends to adapt to modern values and cultural pluralism, while Eastern Islam focuses more on preserving traditions and spiritual values. The aim of this research is to explore the differences and similarities between these two forms of Islamic civilization and their contributions to global civilization. Using a qualitative approach with a literature review design, this study analyzes texts from books, journals, and writings by Islamic scholars from both sides. The findings show that although there are differences in their approaches to modernity, both forms of Islam share common foundational values that can enrich Islamic civilization as a whole. The implications of this study emphasize the importance of collaboration between Western and Eastern Islam to address globalization challenges and create an inclusive and sustainable civilization.